2005
DOI: 10.1247/csf.30.35
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Form of Heparin-binding EGF-like Growth Factor Contributes to Retinoic Acid-induced Epidermal Hyperplasia

Abstract: ABSTRACT. Heparin-binding EGF-like growth factor (HB-EGF), a member of the EGF-family, is thought to be important for keratinocyte functions. HB-EGF is first synthesized as a membrane-anchored form, and its soluble form is released by ectodomain shedding. Here we investigate the role of HB-EGF in epidermal hyperplasia induced by all-trans retinoic acid (tRA) treatment. HB-EGF is normally expressed in epidermis of normal adult mice at very low levels, but topical tRA treatment results in epidermal hyperplasia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…Furthermore, immunoblotting of WT HB-EGF and HB-HB obtained from the all-trans retinoic acid-treated back skin of WT and HB hb/hb mice, respectively, showed comparable protein induction (see Fig. S5G in the supplementary material), similar to that of previously described knock-in mice expressing an uncleavable proHB-EGF mutant (HB uc/uc mice) Kimura et al, 2005). …”
Section: Generation Of Mice Expressing An Hb-egf Truncation Mutant Thsupporting
confidence: 83%
“…Furthermore, immunoblotting of WT HB-EGF and HB-HB obtained from the all-trans retinoic acid-treated back skin of WT and HB hb/hb mice, respectively, showed comparable protein induction (see Fig. S5G in the supplementary material), similar to that of previously described knock-in mice expressing an uncleavable proHB-EGF mutant (HB uc/uc mice) Kimura et al, 2005). …”
Section: Generation Of Mice Expressing An Hb-egf Truncation Mutant Thsupporting
confidence: 83%
“…Only a limited number of studies have investigated these issues. For example, previous studies have demonstrated that HB-EGF contributes to mouse heart muscle homeostasis and trans-retinoic-acid-induced skin hyperplasia (Kimura et al, 2005) through ErbB2-ErbB4 and ErbB1-ErbB2 heterodimers, respectively. HB-EGF and TGFα have been shown to synergistically contribute to skin epithelial sheet migration in mouse eyelid closure (Mine et al, 2005) and alveolar development (Minami et al, 2008) through ErbB1, although the partner of ErbB1 has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…(21) HB-EGF gene expression has been demonstrated in a variety of tissues, predominantly the lung, heart, brain and skeletal muscle. (22) HB-EGF participates in a variety of physiological and pathological processes, (11) including wound healing, (23) eyelid formation, (24) blastocyst implantation, (25) retinoic acid-induced epidermal hyperplasia (26) and atherosclerosis. (27) Recently, HB-EGF knockout mice have been established.…”
Section: Structure and Physiological Functions Of Hb-egfmentioning
confidence: 99%